Simfoni Kidung Tanggulangin: From Us to Keswa - satrya, al rosyid anggi; Almaida, Zwita; Miracahyani, Adhelia Hasri (Prospect Publishing, 2024)
Mental illness often becomes a turning point in a person's life. The strong social stigma and the double burden that mental health patients must bear make them vulnerable to isolation and discrimination. The CSR program of Pertamina Gas Operation East Java Area, titled